Macrospin model of magnetization dynamics governed by Landau-Lifshitz-Bloch equation of motion - Kılıç, Ufuk. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
The main physical limitation in the down-scaling of magnetic data storage technologies, namely the superparamagnetic effect, can be pushed back considerably by using high perpendicular magnetic anisotropy materials. The lack of understanding of the nature of such switching dynamics of magnetic bits especially close to Curie temperature (TC) led to the development of a new formalism that takes into account both longitudinal and transverse magnetization relaxation mechanisms in addition to temperature dependent damping parameters. All such e ects are conventionally disregarded within the Landau-Lifshitz-Gilbert framework. In our study, we point out significant changes in the switching process close to TC using the recently proposed stochastic Landau-Lifshitz-Bloch formalism which takes into account thermal excitations at elevated temperatures by including Gaussian stochastic processes. The essential motivation of current work is to develop a Stochastic-LLB based macrospin model, using experimentally measured temperature dependence of intrinsic parameters for an example magnetic system CoNi/Pd multilayers as realistic material parameters. Such a model enables us to determine the temperature dependence of longitudinal susceptibility from single fit simulations of experimental switching data consistent with previous ab-initio calculations. A map of switching time as a function of magnetic field and heating pulses together with a visualization of granular switching process is presented for the evaluation of this and similar material systems for potential thermally assisted recording applications. While using a simple macrospin approach appears effective in describing the average behavior of strongly exchange- coupled magnetic MLs, a good understanding of the detailed switching mechanism and the role of geometry when patterned into nanoscale structures would necessitate an extension of our model to the micromagnetic simulations.
Keywords: Magnetization.; Spin waves.